COMPARISON OF TOOTH CROWNS AND ROOTS BETWEEN BANJARESE AND JAVANESE PATIENTS AT GUSTI HASAN AMAN DENTAL HOSPITAL - Bayu Indra Sukmana; Huldani Huldani; Anugrah Qatrunnada Hakim (Dentino : Jurnal Kedokteran Gigi, 2020)
Background: Comparison between crowns and roots of the teeth has an important role in determining treatment planning in orthodontics and prosthodontics field. Indonesia, an archipelagic state with diverse ethnicities, is dwelled by 1.300 ethnic categories distributed in various islands including Kalimantan and Java based on the 2010 population census. Javanese is one ethnicity classified in Deutro-Malay sub-race as the result of miscegenation between Proto-Malay sub-race and Mongoloid race. Banjarese, contrarily, is derived from Proto-Malay race which based on Radam theory is originated from a low-lying area adjacent to rivers. There is an urge to examine the comparison of tooth crowns and roots between Javanese and Banjarese due to different racial origin that may greatly influence the treatment plan and prognosis of dental care. Objective: To analyze the differences in roots and crowns length of teeth between Javanese and Banjarese. Methods: All medical records of outpatients in all departments in GustiHasanAman Dental Hospital from 2018 to 2019 were examined and status card from Javanese and Banjarese patients were preferred. Result: The result of tooth roots and crowns comparison in Javanese and Banjarese outpatients at GustiHasanAman Banjarmasin Dental Hospital showed that there were differences in root and crown length between Javanese and Banjarese patients. Comparison of tooth roots and crowns between Javanese was 0.719 and Banjarese was 0.838. It can be concluded that there is a significant difference in the comparison of tooth crowns and roots between Javanese and Banjarese in GustiHasanAman Banjarmasin Dental Hospital.